2018
DOI: 10.1186/s12879-018-3034-8
|View full text |Cite|
|
Sign up to set email alerts
|

Public health impact and cost effectiveness of routine childhood vaccination for hepatitis a in Jordan: a dynamic model approach

Abstract: BackgroundAs the socioeconomic conditions in Jordan have improved over recent decades the disease and economic burden of Hepatitis A has increased. The purpose of this study is to assess the potential health and economic impact of a two-dose hepatitis A vaccine program covering one-year old children in Jordan.MethodsWe adapted an age-structured population model of hepatitis A transmission dynamics to project the epidemiologic and economic impact of vaccinating one-year old children for 50 years in Jordan. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The conspicuous epidemiologic shift in HAV sero-prevalence with a decline in HAV IgG positivity in younger age groups was also reported in a review by Melhem et al in the MENA countries [36]. Thus, the observation of such a decline in this study appears as an expected result and puts a further emphasis on the possible benefit of HAV vaccination in Jordan [27]. This is particularly important in Jordan, considering the current instabilities in the region, which was accompanied by population displacements involving refugees settling in heavily populated camps with poor sanitation and access to clean drinking water [37][38][39].…”
Section: Discussionsupporting
confidence: 85%
“…The conspicuous epidemiologic shift in HAV sero-prevalence with a decline in HAV IgG positivity in younger age groups was also reported in a review by Melhem et al in the MENA countries [36]. Thus, the observation of such a decline in this study appears as an expected result and puts a further emphasis on the possible benefit of HAV vaccination in Jordan [27]. This is particularly important in Jordan, considering the current instabilities in the region, which was accompanied by population displacements involving refugees settling in heavily populated camps with poor sanitation and access to clean drinking water [37][38][39].…”
Section: Discussionsupporting
confidence: 85%
“…We found that 16 cost-per-QALY studies (1.4%) reported a total of 68 cost-per-QALY ratios from a healthcare sector and a societal perspective (34 ratios from each perspective), and five cost-per-DALY studies (0.7%) reported a total of 72 cost-per-DALY ratios (36 ratios from each perspective). Seven of 16 cost-per-QALY studies reported one ratio from each perspective [28][29][30][31][32][33][34], whereas two studies reported five and six intervention-specific ratios from each perspective, respectively [35,36]. Four of five cost-per-DALY studies reported one or two ratios from each perspective [37][38][39][40], and one multicountry study reported 31 ratios from each perspective [41].…”
Section: Main Analysis 3: the Use Of Impact Inventory And Multiple Perspectivesmentioning
confidence: 99%
“…Studies reported that the use of quantitative methods in geographical settings where datasets were of weak quality called for adapted solutions. In our review, studies showed alternative avenues for impact modelling, for instance, to make up for the lack of incidence data [86,97]. In qualitative HIAs, different data collection methods were employed, including the use of participatory approaches such as stakeholder e-interviews [112], and news virtual tools such as Google Earth were applied [119].…”
Section: Discussionmentioning
confidence: 99%